Performance and Reproductive Ripitability Value of Holstein Friesian Dairy Cattle in South Garut Farmers Cooperative - Nuraeni, Ina; Indrijani, Heni; Solihati, Nurcholidah (Fakultas Peternakan, Universitas Padjadjaran, 2025)
The purpose of this study was to determine the performance and repeatability values of S/C, DO, and CI in the South Garut Farmers Cooperative. Reproduction data used were individual reproduction records of 162 Friesian Holstein dairy cows. The results showed that the average reproductive performance for S/C for parity 1 was 2.20 ± 0.797, parity 2 was 2.40 ± 0.974, parity 3 was 2.28 ± 0.947, parity 4 was 2.22 ± 0.965, and the total value of S/C was 2.28 ± 0.921. The DO value for parity 1 was 159.50 ± 80.838, parity 2 was 150.43 ± 73.874, parity 3 was 142.29 ± 56.689 days, parity 4 was 133.79 ± 42.678 days, and the total DO was 146, 50 ± 67.267 days. The CI value for parity 1 was 437.91 ± 80.144 days, parity 2 was 430.20 ± 75.211 days, parity 3 was 423.31 ± 57 days, parity 4 was 414.59 ± 42.470 days, and the total CI was 426, 5 ± 67.355 days. The repeatability value at KPGS for S/C was 0.17 ± 0.033, DO was 0.1 ± 0.040, and CI was 0.097 ± 0.040. These three reproductive properties show repeatability values in the low category